Interviewing Francesco Tonucci (Journal of Parents and Teachers, 2014)
In this issue of Padres y Maestros, an interview with the renowned Italian pedagogue Francesco Tonucci is offered. He gives his opinion on the rights of the children or the importance of the game, among other aspects.
Keywords: interview; Francesco Tonucci; children.